Financial inclusion and inclusive growth in sub-Saharan Africa - Bernard Sarpong; Edward Nketiah-Amponsah (Cogent Economics & Finance)
This paper empirically examines the quantitative relationship between financial inclusion and inclusive growth in sub-Saharan Africa using a panel of 46 countries for the period 2004–2018. The evidence suggests that usage of financial services, among other covariates, has a quantifiable and discernible impact on inclusive growth compared with availability and knowledge of financial services. Precisely, a unit increase in the usage of financial products and services improves inclusive growth by 0.03 units in sub-Saharan Africa. The paper contributes to literature by initially constructing a broader index of inclusive growth and subsequently estimating the separate quantitative effects of three categories of financial inclusion indicators on inclusive growth by employing the Arellano–Bover/Blundell–Bond system Generalized Method of Moment estimator. The findings underscore the need for policymakers to develop innovative, sustainable and inclusive financial systems capable of distributing growth benefits equitably. This can be achieved through moderate lending rates and transaction charges, improved access to retail and corporate loans, mortgages, overdrafts, credit cards, letters of credits and user-friendly financial technologies.